CORPORATION’S CARBON NEUTRALITY INITIATIVE: THE ROLE OF DATA ENGINEERING IN DRIVING SUSTAINABILITY - Satish Kumar Boddu (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The corporation has embarked on an ambitious initiative to achieve carbon neutrality across its entire value chain by the end of this decade. At the heart of this transformation lies the strategic implementation of advanced data engineering techniques, enabling precise carbon accounting, optimized supply chain operations, and innovative energy management solutions. This comprehensive article explores the pivotal role of data engineering in advancing Corporation's sustainability objectives while creating broader societal impact. The article examines the sophisticated architecture, tools, and methodologies employed to measure and mitigate carbon emissions, presenting a scalable framework that other organizations can adopt in their sustainability journey.